The effect of pharmacological treatment on gait biomechanics in peripheral arterial disease patients - Huisinga, Jessie M (BioMed Central, 2010)
BACKGROUND: Pharmacological treatment has been advocated as a first line therapy for Peripheral Arterial Disease (PAD) patients suffering from intermittent claudication. Previous studies document the ability of pharmacological treatment to increase walking distances. However, the effect of pharmacological treatment on gait biomechanics in PAD patients has not been objectively evaluated as is common with other gait abnormalities. METHODS: Sixteen patients were prescribed an FDA approved drug (Pentoxifylline or Cilostazol) for the treatment of symptomatic PAD. Patients underwent baseline gait testing prior to medication use which consisted of acquisition of ground reaction forces and kinematics while walking in a pain free state. After three months of treatment, patients underwent repeat gait testing. RESULTS: Patients with symptomatic PAD had significant gait abnormalities at baseline during pain free walking as compared to healthy controls. However, pharmacological treatment did not produce any identifiable alterations on the biomechanics of gait of the PAD patients as revealed by the statistical comparisons performed between pre and post-treatment and between post-treatment and the healthy controls. CONCLUSIONS: Pharmacological treatment did not result in statistically significant improvements in the gait biomechanics of patients with symptomatic PAD. Future studies will need to further explore different cohorts of patients that have shown to improve significantly their claudication distances and/or their muscle fiber morphology with the use of pharmacological treatment and determine if this is associated with an improvement in gait biomechanics. Using these methods we may distinguish the patients who benefit from pharmacotherapy and those who do not.